A corpus-assisted study of the discourse marker well as an indicator of judges' institutional roles in court cases with litigants in person. Issue 2 (August 2015) - Tkačuková, Tatiana
<x content-type="archive" xml:space="preserve">Abstract</x> In this paper, I concentrate on court cases with litigants in person (lay people who act on their own behalf in legal proceedings without a counsel or solicitor) and discuss the challenges of building a corpus of courtroom discourse where it is crucial to distinguish between speakers due to their distinct institutional roles. The corpus incorporates seven sub-corpora of verbatim transcripts from different court cases with litigants in person and comprises over eleven-million tokens. The focus of this paper is on the interplay between the legal and lay discourse types and how judges project their institutional roles through well-initiated turns directed at litigants in person and counsels. As a versatile discourse marker, well provides a good opportunity to explore how judges have to adapt their roles to ensure lay litigants in person receive the necessary support and that their lack of competence does not impede on the fairness of the proceedings. Given the breadth and importance of the topic of litigation in person, I discuss how the tools and approaches of corpus linguistics can be helpful in this multi-disciplinary area where multiple functions and uses of individual linguistic features need to be explored in depth.